Diffuus erfgoed in kaart: het DRAPO-project - Leerssen, Joep; Lucassen, Doortje (Studies over de sociaaleconomische geschiedenis van Limburg, 2022)
Flags are an important element in the visual self-display of Limburg associational life. The DRAPO project presented here aimed to inventorize these objects and map them into a database. The DRAPO project aimed to put a number of scholarly and archival challenges to the test: [1] devising a visual and analytical dataset of material culture, with descriptive and analytical power for curators and academics as well as a low-threshold accessibility for the general user; [2] allowing a ‘citizen science’ component: making active participation from the general public possible by integrating upload and addition possibilities into the Public User Interface; [3] devising the dataset in such an open relational structure that further integration with Linked Open Data datasets (in existence and in development) is possible. Use was made of Nodegoat, a web-based research environment for the humanities, to capture the objects and metadata and to allow for an interactive visualization of the underlying patterns.